2010
DOI: 10.1093/cercor/bhq209
|View full text |Cite
|
Sign up to set email alerts
|

Motor Learning with Augmented Feedback: Modality-Dependent Behavioral and Neural Consequences

Abstract: Sensory information is critical to correct performance errors online during the execution of complex tasks and can be complemented by augmented feedback (FB). Here, 2 groups of participants acquired a new bimanual coordination pattern under different augmented FB conditions: 1) visual input reflecting coordination between the 2 hands and 2) auditory pacing integrating the timing of both hands into a single temporal structure. Behavioral findings revealed that the visual group became dependent on this augmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
154
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(171 citation statements)
references
References 73 publications
13
154
2
2
Order By: Relevance
“…Clearly, this kind of concurrent visual feedback is at its most effective when the learner is deprived of some awareness of the fundamental kinematics of the motor task in question. Kovacs et al [35] did not test retention without feedback, but one can be fairly confident based on related studies [27,39] that a pronounced guidance effect would be evident. In the case of Lissajous-style feedback, what was originally intended as a guide to help learning an action has swallowed the task to be learned, replacing it completely.…”
Section: Section 2: Factors That Influence the Ef-fectiveness Of Augmmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, this kind of concurrent visual feedback is at its most effective when the learner is deprived of some awareness of the fundamental kinematics of the motor task in question. Kovacs et al [35] did not test retention without feedback, but one can be fairly confident based on related studies [27,39] that a pronounced guidance effect would be evident. In the case of Lissajous-style feedback, what was originally intended as a guide to help learning an action has swallowed the task to be learned, replacing it completely.…”
Section: Section 2: Factors That Influence the Ef-fectiveness Of Augmmentioning
confidence: 99%
“…The source of feedback upon which a learner had previously relied is no longer available to guide performance, and the learner must reweight to a comparatively unused source. The result is impaired performance-monitoring ability [27]. The ability to detect signals corresponding to both good and bad performance using internal monitoring mechanisms (i.e.…”
Section: Section 1: Motor Learning and Aug-mented Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the correction time should be decreased if there is no improvement in the accuracy of motion. Ronsse et al [23] reported that the effectiveness of motor learning with the use of visual feedback was decreased over time with periodic flexion and extension at both wrist joints. Ohashi et al [24] reported that the information pertaining to the intensity of force in an isometric contraction task was decreased over the course of time.…”
Section: The Effect Of Motor Imagery On the Accuracy Of Motionmentioning
confidence: 99%
“…Wallis et al [60] implemented real-time motion sonification using music to impart movement in stroke rehabilitation tasks. Ronsse et al [61] demonstrated that for the pacing and temporal coordination of hand movements during complex bimanual tasks, real-time audio feedback can outperform visual feedback in terms of skill retention. When asked to complete the task without feedback, participants who had received visual feedback retained less of the coordination learned in training than those with audio feedback.…”
Section: Audiomentioning
confidence: 99%